Colorado water, February 2022 - Mokry, Melissa, editor; Colorado Water Center, publisher (Colorado State University. Libraries, 2022)
Newsletter of the CSU Water Center. Theme: InTERFEWS, Interdisciplinary Training, Education and Research in Food-Energy-Water Systems.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water supply -- Colorado; Water use -- Colorado; Water supply -- Management -- Colorado